2022
DOI: 10.31004/prepotif.v6i1.3171
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pengetahuan Dan Sikap Dengan Kepatuhan Penggunaan Alat Pelindung Diri Pekerja Bagian Pengolahan Aspal Di Jalan Raya Kecamatan Medan Sunggal

Abstract: ABSTRACT The obedience of the worker in obeying the use of apd is determined by two factors which are individual and work factors, obedience to the use of apd is determined by knowledge in the worker, as the working day will affect the quantity and quality of the worker to the job. Worker knowledge will change behavior so that a change of attitude will create a worker's attitude to conform to the rules of the job. The aim of this research is to analyze the relationships of knowledge and worker behavior w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
1
1
1
4
Order By: Relevance
“…The results of this study are supported by the previous research carried out by Ambarita, Suryoputro and Setyaningsih (2022) and Rahmawati, Romdhona, and Fauziah (2022) that education and PPE compliance do not significantly correlate. This is in contrast to the research conducted by R. Rahmawati & Pratama, (2019) on 85 respondents with a POR of 4.796, which means that respondents with a low level of education have a risk of 4.796 times to be non-compliant in the use of PPE compared to respondents with higher education. It is suspected respondents in the high education level group are not compliant with the use of PPE because they believe that long experience in the job is the reason, whereas respondents in the low education level group are compliant with the use of PPE because they follow current regulations and are aware of a small risk if they do not use PPE.…”
Section: Relationship Between Education With Compliance With the Use ...contrasting
confidence: 81%
See 2 more Smart Citations
“…The results of this study are supported by the previous research carried out by Ambarita, Suryoputro and Setyaningsih (2022) and Rahmawati, Romdhona, and Fauziah (2022) that education and PPE compliance do not significantly correlate. This is in contrast to the research conducted by R. Rahmawati & Pratama, (2019) on 85 respondents with a POR of 4.796, which means that respondents with a low level of education have a risk of 4.796 times to be non-compliant in the use of PPE compared to respondents with higher education. It is suspected respondents in the high education level group are not compliant with the use of PPE because they believe that long experience in the job is the reason, whereas respondents in the low education level group are compliant with the use of PPE because they follow current regulations and are aware of a small risk if they do not use PPE.…”
Section: Relationship Between Education With Compliance With the Use ...contrasting
confidence: 81%
“…Workers who are given training will have a higher possibility to comply with the use of PPE compared to workers who are not (Zegeorgous et al, 2020). This is in line with the research conducted by Rahmawati and Pratama (2019) which found a relationship between training and compliance with the use of PPE with the results of a p-value of 0.000 <0.05 and a statistical result of POR = 9.583 which means that respondents who have never attended training are at risk 9.5 times to be non-compliant in using PPE compared to respondents who attend training. A person's behavior can be influenced by training because it involves altering ingrained behavioral patterns, which will ultimately result in behavioral changes.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Penelitian ini juga sejalan dengan penelitian Pratama bahwa terdapat hubungan antara pendidikan dengan ISSN Print : 2442-5885 Journal homepage: http://afiasi.unwir.ac.id ISSN Online : 2622-3392 9 kepatuhan penggunaan APD. 18 Yakni pendidikan menjadi faktor yang mendukung tenaga kerja patuh menggunakan APD, yang artinya pekerja berupaya memelihara kesehatannya dan melindungi diri dari risiko bahaya. Tingkat pendidikan juga merupakan gambaran tentang pengetahuan dan wawasan yang dimiliki, semakin tinggi pendidikan maka dianggap lebih tahu dan lebih benar dalam pemikiran, hal ini juga menentukan tingkat sosial ekonomi seseorang dalam masyarakat.…”
Section: B Pendidikanunclassified
“…3 Penelitian ini juga tidak sejalan dengan penelitian Pratama yang menyatakan bahwa responden yang tidak pernah mengikuti pelatihan, berisiko untuk tidak patuh dalam menggunakan APD dibandingkan dengan responden yang pernah mengikuti pelatihan. 18 Penelitian ini sejalan dengan penelitian yang dilakukan Putri yang menyatakan bahwa tidak terdapat hubungan antara pelatihan dengan kepatuhan penggunaan APD. 17 Begitu juga dengan penelitian Ramadhany dan Terry yang menyatakan bahwa tidak ada hubungan yang signifikan antara pelatihan K3 dengan tindakan tidak selamat (unsafe act).…”
Section: Pelatihanunclassified